FAKTOR PREDISPOSISI DAN PRESIPITASI BERHUBUNGAN DENGAN KEKAMBUHAN PASIEN GANGGUAN JIWA DI PUSKESMAS PEGANG PANTI PASAMAN TAHUN 2017 - Isna Ovari; Muhammad Ikhwan (JURNAL KESEHATAN PERINTIS, 2018)
Mental disorder is syndrome or pattern of behavior or psikologik one is enought meaningful clinic and typical pertaining to asymptom or disruption in one or morefunction the importance of man. A recurrence disease usually caused by the it relapse patients treatment. Research aimsto understand what is the relationship betweeen factors predisposing, precipitation by relapse mental disorder patients in Kenagarian Pegang Baru Panti Pasaman. Research has done April in 2017, a design study descriptive shaped analytic with and the number of respondents the 55. The statistic used is chi square on the meaning 0,05. The result showed more than half of respondents mental disorder the faktor predisposing dominate the 65,5 %. And the more than half of respondents mental disorder the faktor precipitation that is not dominant 52,7 %. More than half of respondents mental disorder experienced a recurrence namely 52,7%. So conclusion of this research is there was a correlation between factors predisposing by a relapseiomental disorder patients with the p = 0,036. And there was a correlation factors precipitation by a relapse mental disorder patients with the p = 0,042. Based on the results of abovein suggest to nurses mental health in community to do home visit who regular and give routine activity for patients to a recurrence diseases could continue to sent down.